Management of hypertension in chronic kidney disease: current perspectives and therapeutic strategies - Alsalloum, Muath A.; Albekery, Mohamed A.; Alhomoud, Ibrahim S. (Frontiers in Medicine, 2025)
Hypertension in chronic kidney disease (CKD) is a major health challenge, with cardiovascular disease being the major cause of mortality in CKD. Several factors play a role in its pathophysiology, including renin-angiotensin system activation. Guidelines for blood pressure management in CKD patients demonstrate some variation in their recommended targets and therapeutic approach. However, current practice increasingly adopts stricter systolic blood pressure target when tolerable. A daily sodium intake of less than 2 grams and engagement in moderate-intensity physical activity (≥30 min, 5–7 days per week) are strongly recommended. However, the majority of patients with CKD ultimately require combination therapy with multiple antihypertensive agents, such as calcium channel blockers (CCBs) and thiazide or thiazide-like diuretics. Recent evidence is increasingly in favor of considering sodium-glucose cotransporter-2 (SGLT-2) inhibitors, incretin therapies, and mineralocorticoid receptor antagonists (MRAs), given their established benefits on cardiovascular and kidney-related outcomes, even though their blood pressure lowering effects remains relatively modest. Emerging agents with novel mechanisms of action, such as endothelin receptor antagonists, are also under investigation and may provide additional therapeutic options in the future. This review aims to summarize current guideline recommendations and therapeutic strategies for managing hypertension in CKD, including recent and emerging pharmacologic approaches.